The Contributions of Cognitive Individual Differences on EFL Productive Skills through Online Instruction - Salimian Rizi, Mohsen; Yazdani, Hooshang (JOLLT Journal of Languages and Language Teaching, 2022)
Although there is adequate research about learning style and motivation in face-to-face classes, there is still a scarceness of available studies exploring such individual differences in EFL online settings and to the best knowledge of the researcher, no previous studies even try to address their impacts on EFL learners' productive skill in online EFL classroom settings. To this end, this study which is one of the newest in this field aimed at increasing our understanding of the contribution of such cognitive individual differences on EFL productive skills through online instruction using concurrent triangulation design. The results demonstrated that out of the two cognitive individual differences, the strongest association was observed between the motivation variable and EFL productive skills. Nevertheless, unlike other studies the relation between learning style use and EFL productive skills proficiency was not significant. The implications of the study will instill new insights for EFL researchers and language learners to consider the recent pandemic as a blessing in disguise, acting as a foundation stone towards online EFL instruction advancement in the Iran. Also, since motivation impact language achievement significantly, building a learner-friendly and encouraging atmosphere in online settings is therefore vital.